2009
DOI: 10.1159/000207555
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-α for Treatment of Essential Thrombocythemia during Pregnancy: Case Report and Review of the Literature

Abstract: Described as a myeloproliferative disorder mainly affecting elderly women, recent reports now confirm the occurrence of essential thrombocythemia at younger ages, which questions treatment during pregnancy. We report a further case of uneventful full term pregnancy with the use of interferon-α for maternal essential thrombocythemia which suggests that interferon-α could be considered as an effective and safe treatment during pregnancy for women with essential thrombocythemia. Further studies are warranted to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…IFN-a is a biological response-modifying cytokine with both myelosuppressive and immunomodulatory effects. IFN-a, may be a particularly appropriate treatment for pregnant women (53) or those planning pregnancy as it is not associated with teratogenic effects or adverse effects on male fertility. Unfortunately, IFN-a therapy is associated with significant side effects that include flu-like symptoms (such as chills and fever) as well as fatigue, headache, diarrhoea and a range of other haematological and autoimmune symptoms (40,54).…”
Section: Interferon-a (Ifn-a)mentioning
confidence: 99%
“…IFN-a is a biological response-modifying cytokine with both myelosuppressive and immunomodulatory effects. IFN-a, may be a particularly appropriate treatment for pregnant women (53) or those planning pregnancy as it is not associated with teratogenic effects or adverse effects on male fertility. Unfortunately, IFN-a therapy is associated with significant side effects that include flu-like symptoms (such as chills and fever) as well as fatigue, headache, diarrhoea and a range of other haematological and autoimmune symptoms (40,54).…”
Section: Interferon-a (Ifn-a)mentioning
confidence: 99%
“…The pegylated IFN-α was commenced on her. IFN-α is a safe drug that can be used throughout gestation with no adverse effect on the fetus [2], [9], [10], [22], [23]. IFN-α inhibits cell proliferation through its effect on protein synthesis, RNA breakdown, and possibly by immunomodulation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, INF-α is nonleukemogenic, nonteratogenic, not detected in the amniotic fluid or in fetal blood at the doses used. 73 • Approved treatment of non-cirrhotic paediatric patients ≥ 3 years of age with HBeAg-positive CHB and evidence of viral replication and elevations in serum ALT. • Pregnancy category C: Animal studies have revealed evidence of teratogenicity.…”
Section: Interferon Alpha-2amentioning
confidence: 99%